Effectiveness of Music Therapy in Reducing Anxiety Among Patients Undergoing Hemodialysis: A Literature Review of Complementary Care Approaches - Sari, Putri Irwanti; Annisa, Febri; Jasman, Luthfiah; Farhah, Nawal; Ningsih, Novi Setyo; Putri, Revanya Dwi Herdian; Khoirunisya, Siti (Jurnal Pinang Masak, 2026)
Introduction: Anxiety is a psychological problem that is often experienced by patients with chronic kidney failure who are undergoing hemodialysis. Research shows that nearly half of hemodialysis patients experience abnormal anxiety, and about 25% are in the borderline category. The high prevalence of anxiety is related to the physical and emotional burden during long-term hemodialysis therapy. This condition confirms the need for effective nonpharmacological interventions, one of which is music therapy. Objective: This study aims to collect and analyze scientific evidence related to the effectiveness of music therapy in reducing anxiety in patients with chronic kidney failure undergoing hemodialysis in the context of a palliative approach. Methods: This study uses a literature review method by examining articles published in 2023–2025 obtained through PubMed and Searching Engine, Mesh. The search was conducted using keywords related to music therapy and anxiety in hemodialysis patients. A total of 10 articles met the inclusion criteria and were systematically analyzed to assess the research design, anxiety instruments, type of music, and the results of the intervention. Results: Based on the article analyzed, music therapy was shown to be effective in reducing anxiety in hemodialysis patients. This intervention is effective as a nonpharmacological method because it provides a relaxation effect, is easy to apply, is cost-effective, and can be adjusted to the patient's needs. Conclusion: Music therapy has the effectiveness to be used as an effort to reduce anxiety in patients undergoing hemodialysis.